Low latency carbon budget analysis reveals a large decline of the land carbon sink in 2023 - Ke, Piyu; Ciais, P.; Sitch, S.; Li, Wei; Bastos, Ana; Liu, Zhu; Xu, Yidi; Gui, Xiaofan; Bian, Jiang; Goll, D.; Xi, Yi; Li, Wanjing; et al. (National Science Review, 2024)
In 2023, the CO2 growth rate was 3.37 ± 0.11 ppm at Mauna Loa, 86% above the previous year, and hitting a record high since observations began in 1958, while global fossil fuel CO2 emissions only increased by 0.6 ± 0.5%. This implies an unprecedented weakening of land and ocean sinks, and raises the question of where and why this reduction happened. Here we show a global net land CO2 sink of 0.44 ± 0.21 GtC yr−1, the weakest since 2003. We used dynamic global vegetation models, satellites fire emissions, an atmospheric inversion based on OCO-2 measurements, and emulators of ocean biogeochemical and data driven models to deliver a fast-track carbon budget in 2023. Those models ensured consistency with previous carbon budgets. Regional flux anomalies from 2015–2022 are consistent between top-down and bottom-up approaches, with the largest abnormal carbon loss in the Amazon during the drought in the second half of 2023 (0.31 ± 0.19 GtC yr−1), extreme fire emissions of 0.58 ± 0.10 GtC yr−1 in Canada and a loss in South-East Asia (0.13 ± 0.12 GtC yr−1). Since 2015, land CO2 uptake north of 20°N declined by half to 1.13 ± 0.24 GtC yr−1 in 2023. Meanwhile, the tropics recovered from the 2015–16 El Niño carbon loss, gained carbon during the La Niña years (2020–2023), then switched to a carbon loss during the 2023 El Niño (0.56 ± 0.23 GtC yr−1). The ocean sink was stronger than normal in the equatorial eastern Pacific due to reduced upwelling from La Niña's retreat in early 2023 and the development of El Niño later. Land regions exposed to extreme heat in 2023 contributed a gross carbon loss of 1.73 GtC yr−1, indicating that record warming in 2023 had a strong negative impact on the capacity of terrestrial ecosystems to mitigate climate change.